Pengembangan Perumahan Dengan Desain Konstruksi Dilahan Basah Pada Wilayah Kota Banjarmasin Menggunakan Riset Operasi - Eliatun Eliatun; Darmansyah Tjitradi (Jurnal Teknik Sipil, 2018)
The condition of soil in Banjarmasin which is dominated by wetland with a soil bearing capacity of as low as 0.2 kg/cm2 means that buildings require costly foundations. This condition requires that developers be more selective and perform optimisation in choosing types of soft-soil foundations to ensure maximum profit from the building investment. The objective of this research is to optimise the use of a given building area by assigning different types of sub-structure subject to a number of constraints. Optimization is used by operations research methods which are solved by Integer Programming Software QM for Windows version 2.1 and is based on the development of a housing fictitious data X type-36 in Banjarmasin. The analysis result showed that the composition of the optimum number of types of houses built is for type-A 30 units, type-B 17 units, and type-C 20 units with maximum profit of Rp.4,000,000,000, the required development area is 5,360 m2 with production costs required Rp.20,000,000,000 and the construction time of all types of houses is along 67 weeks.